THEORETICAL FOUNDATIONS OF TECHNOLOGIES FOR THE DEVELOPMENT OF THE LEGAL CULTURE OF FUTURE TEACHERS ON THE BASIS OF AN INNAVATION APPROACH - Mukhamadiyev Dilshod Aslitdinovich (Bright Mind Publishing, 2026)
In this article, the concept of "literacy" expands its content at the modern stage of development of pedagogical science.n this article, the concept of "literacy" expands its content at the modern stage of development of pedagogical science. If for a long time in science, the concept of "elementary literacy" in the quality of an indivi.
Keywords: Rule of law; legal society; legal democratic state; legal education; legal culture; legal consciousness; civic responsibility; patriotism; moral education; future teachers; innovative approach; school-based civic education; spirituality and values; prevention of extremism; youth development; social participation.